Discovery Learning Can Increase Mathematics Learning Outcomes for Class VI Students of SDN Ngroto, Academic Year 2020/2021 - Hapsari, Linda (Universitas Sebelas Maret, 2020)
This study is motivated by several difficulties such as material and learners are still focused on mastery of cognitive knowledge, the learning process of learners is still in the level of C1 (remembering), C2 (understanding), C3 (application) so that it never carries out learning oriented to high-level thinking skills (HOTS). To face the era of the Industrial Revolution 4.0, students must be equipped with high-level thinking skills (High Order Thinking Skills). One of the hots-oriented learning models implemented by the 2013 curriculum is the Discovery Learning model. Learning using the Discovery Learning model can increase the activeness and creativity in learning so that learners feel happy and not bored from the beginning to the end of learning. This is evidenced by an increase in the results of the evaluation of learners' learning from each meeting. At the 1st meeting the completion of students was only 41.7% while at the 2nd meeting increased to 91.7%. Thus it can be concluded that the application of discovery learning model can improve the liveliness and learning outcomes of learners.